PROSEDUR PENGAMBILAN PINJAMAN TANPA AGUNAN DI SALAH SATU BANK BUMN SURABAYA - Nadia Dinda Luthfiyah; Siti Ning Farida (Cahaya Ilmu Bangsa, 2025)
Unsecured loans or Unsecured Credit (KTA) are one of the banking products that offer convenience for customers to get funds without requiring asset collateral. This study aims to examine the procedure for taking unsecured loans at one of Surabaya's state-owned banks, including the stages of document collection, data verification, creditworthiness analysis, and disbursement of funds. Using a qualitative descriptive research method, data was collected through direct observation and interviews with bank administration staff. The results of the study indicate that the procedure for taking unsecured loans has been carried out according to standard operating procedures (SOP), although there are challenges such as completeness of customer documents and efficiency of the administrative process. This study provides insight into the importance of excellent service and digitalization in supporting the unsecured credit process.